Prevalence of gingivitis in patients with open bite - PARTHASARATHY, PREETHA; BABU, HARISH; DHARMAN, SREEDEVI (The journal of contemporary issues in business and government, 2021)
Open bite is defined as a developmental or acquired malocclusion whereby no vertical overlap exists between maxillary and mandibular anterior or posterior teeth. It can either be dental or skeletal open bite; anterior or posterior open bite. Open bite can result in mouth breathing causing changes in the muscular force and can lead to increased susceptibility of gingivitis. The study is conducted to find a correlation between open bite and gingivitis. The aim of the study is to evaluate the prevalence of gingivitis in patients with open bite. This study was based on data collected from the digital database of Saveetha Dental College and Hospitals. Over 86000 patient records were reviewed and analysed over a six month period from September 2019 to February 2019. A total of 1000 case sheets of patients were reviewed. Cross verification of data for error was done by presence of additional reviewers and by photographic evaluation. Simple random sampling was done to minimize sampling bias. After reviewing, 1000 case sheets were filtered based on data required. The final sample size was 703 patients with Open Bite. Male patients had high prevalence of open bite [53.5%] and presence of gingivitis in open bite patients was 63.9%. The age group 21-40 years [35.70%] had high frequency of gingivitis. P value was found to be insignificant >0.05.Within the limits of the study it was observed that male patients had more prevalence for open bite malocclusion and presence of gingivitis. The age group 21-40 years at high frequency of gingivitis prevalence in patients with open bite.